Resettable electronic logic gates based on multimodulated molecular transport junctions - Chen, Ye (2013)
Molecular electronics has generated much excitement among scientists due to the huge size-reduction of electronics by molecular-level control of properties. Molecules are the smallest stable structures imaginable to exceed the foreseen limits of small-scale conventional silicon integrated circuits. Molecular Transport Junction contains molecules attached to metal electrodes at each end to act as an electronic component. Ru-dithienylethylene (Ru-DTE) molecule is employed due to its bi-conductive functionality upon photochromic isomerization. [2nd Award]